2021
DOI: 10.1080/14397595.2021.1899602
|View full text |Cite
|
Sign up to set email alerts
|

Urinary abnormality in mixed connective tissue disease predicts development of other connective tissue diseases and decrease in renal function

Abstract: Objective To clarify the clinical significance of development of urinary abnormality in mixed connective tissue disease (MCTD). Methods Forty-one patients with an initial diagnosis of MCTD, followed at five hospitals between April 1, 2000 and December 31, 2013, were included. The relationship between urinary abnormality and various clinical parameters were retrospectively analyzed. Urinary abnormality was defined as proteinur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Secondly, the immune response of AIH-PBC patients is stronger, resulting in higher IgM than AIH patients, which was consistent with Ma's research [ 29 ]. In addition, we also found that AIH-CTD patients showed a lower level of serum K and MPV (Table 2 ), which may be due to the involvement of kidney and hematopoietic function in CTD patients, resulting in renal tubular acidosis [ 30 ]. In all, the clinical features of AIH complicated with different immune diseases are various.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the immune response of AIH-PBC patients is stronger, resulting in higher IgM than AIH patients, which was consistent with Ma's research [ 29 ]. In addition, we also found that AIH-CTD patients showed a lower level of serum K and MPV (Table 2 ), which may be due to the involvement of kidney and hematopoietic function in CTD patients, resulting in renal tubular acidosis [ 30 ]. In all, the clinical features of AIH complicated with different immune diseases are various.…”
Section: Discussionmentioning
confidence: 99%